An alternative intervention for juvenile hackers? A qualitative evaluation of the Hack_Right intervention - Schiks, J. A. M. (Journal of crime and justice, 2024)
While traditional crime rates are decreasing, cybercrime is on the rise. As a result, the criminal justice system is increasingly dealing with criminals committing cyber-dependent crimes. However, to date there are no effective interventions to prevent recidivism in this type of offenders. Dutch authorities have developed an intervention program, called Hack_Right. Hack_Right is an alternative criminal justice program for young first-offenders of cyber-dependent crimes. In order to prevent recidivism, this program places participants in organizations where they are taught about ethical hacking, complete (technical) assignments and reflect on their offense. In this study, we have evaluated the Hack_Right program and the pilot interventions carried out thus far. By examining the program theory (program evaluation) and implementation of the intervention (process evaluation), the study adds to the scarce literature about cybercrime interventions. During the study, two qualitative research methods have been applied: 1) document analysis and 2) interviews with intervention developers, imposers, implementers and participants. In addition to the observation that the scientific basis for linking specific criminogenic factors to cybercriminals is still fragile, the article concludes that the theoretical base and program integrity of Hack_Right need to be further developed in order to adhere to principles of effective interventions.